Acromegaly: Role of Surgery in the Therapeutic Armamentarium - Gerardo Guinto; Miguel Abdo; Erick Zepeda; Norma Aréchiga; Moisés Mercado (International Journal of Endocrinology)
Acromegaly is a complex disease that requires the intervention of a multidisciplinary team. The most frequent clinical manifestations are growing of distal parts of the body and some areas of the face. Patients may also present arterial hypertension, diabetes mellitus, colonic polyps, cardiomegaly, neurological and endocrine changes secondary to the presence of a GH-secreting tumor in pituitary or extrapituitary origin, or eutopic hypothalamic GHRH hypersecretion and peripheral GHRH hypersecretion. Surgery is the first treatment used for most patients, regardless of the cause. In the great majority of cases, pituitary tumor can be removed through a transsphenoidal approach. Craniotomy is reserved for those cases with giant tumors, particularly when they grow toward the middle or posterior cranial fossa. Best surgical results are obtained when the tumor is confined into the sella turcica or if it has a regular suprasellar extension. When the disease cannot be controlled with surgery, medical treatment is indicated. Somatostatin analogues are included as the first line of medication, followed by dopamine agonist and growth hormone receptors antagonists. Radiation therapy can be also indicated in two main forms for residual tumor with medically refractory patients: radiosurgery for small tumors or fractionated stereotactic radiotherapy for larger ones.